Legal Framework and Challenges Concerning Forensic Evidence in Nigeria - Wakili, Saminu Abacha; Obisesan, Olawunmi Opeyemi; Ekpenisi, Collins; Antai, Godswill Owoche; Umo, Maria Edet (TRUNOJOYO LAW REVIEW, 2025)
Forensic evidence cannot be avoided in modern legal systems; it is used principally for asserting justice. However, there are several challenges that implementing forensic evidence in the judicial processes faces in Nigeria. Attempts to address this persistent problem include issues such as the admissibility of forensic evidence in courts, lack of adequate forensic infrastructure, inadequate examinations, and a lot more procedural inconsistency. Hence, the need to examine the legal provision regarding forensic evidence in Nigeria, the identification of the main core challenges, and possible reform proposals to improve reliability and acceptance in audit processes. The study adopts a doctrinal study method, relying on primary and secondary sources of research material. The study therefore revealed gross loopholes within the corpus of legislation in Nigeria: highly limited statutory references on emerging forensic technologies, extremely few forensic laboratories, and inconsistencies in judiciary interpretation of forensic evidence. The study has further uncovered a critical blockage to the usage of forensic evidence, which is the lack of specialized training to law enforcement and judiciary officers. The study further concludes that the status of Nigeria as far as the advancement of forensic evidence is concerned is marginally high, but there are lots of things to be done. Legislative amendments are recommended to strengthen forensic vidence laws, investments in forensic infrastructure, and capacity-building initiatives for legal and law enforcement professionals. These measures are sure to strengthen the place of forensic evidence in the advancement of justice in Nigeria.